Paradigmaváltás az energiagazdaságban - Bank, Klára (Közép-Európai Közlemények, 2009)
The fact that the fossil fuels are getting more expensive all around the world most probably will cause certain difficulties in the energy supply of Hungary. Promoting the use of renewable energy resources in our country is vital. We don’t have to pay to foreign countries for them and we can employ Hungarian workforce while producing renewable energy resources. We are concerned about the risks while using renewable energy resources and we take full responsibility for them. The expansion of use of renewable energy resources relies fully on economic productivity. The lack of capital, the biggest problem in Hungary, doesn't give much of a hope either. Still every single consumer should see that a lot of money should be spent on the use of these local resources on the short term. This constraint must be widely known by the population. Economic progress demands from everyone to use renewable energy resources as frequently as possible, though these may seem more expensive than the traditional energy sources.